Greek Gods and Ancient Mortals ‘Resurrected’ in Terracotta Figurines Discovered in Turkey - Yasemin Saplakoglu (Les Carnets de l’ACoSt)
As reported in Live Science, February 14, 2021. Archaeologists have discovered dozens of terracotta figurines that are over 2,000 years old, including ones that depict gods, goddesses, men, women, cavalry and animals. Some of the figurines still had paint on them and some had inscriptions — and all opened a window into life in the ancient town of Myra, in what is now modern-day Demre in Turkey.